2018
DOI: 10.1021/acs.cgd.7b01206
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals Mitigate Negative Effects of High pH on Solubility and Dissolution of a Basic Drug

Abstract: Weakly basic drugs are predisposed to order of magnitude decreases in solubility and dissolution as pH increases from 1 to 7 along the gastrointestinal tract. Such behavior is known to be detrimental to drug absorption. The work presented here shows how cocrystals of basic drugs with acidic coformers can mitigate these negative effects. Cocrystals of ketoconazole (KTZ) with adipic, fumaric, and succinic acids exhibit a parabolic solubility dependence on pH such that with increasing pH, solubility decreases, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…The cocrystal solubilization can be quantified by the AUC (area under the curve), thus constituting a parameter indicative of the influence that cocrystals have on the API performance. The AUC is directly and inversely proportional to the dissolution and precipitation rates, respectively [49]. Figure 7 shows that unformulated NTZ-SUC cocrystals and NTZ-SUC formulated with 1.0% w/w Methocel ® 60 HG do not lead to improved dissolution profiles when compared to NTZ and the Figure 6a illustrates the dissolution profiles measured over a time interval of 3 h of the unformulated (0.0% w/w of Methocel ® 60 HG) solid phases of pure NTZ, the physical mixture with SUC and the NTZ-SUC cocrystal.…”
Section: Of 18mentioning
confidence: 99%
“…The cocrystal solubilization can be quantified by the AUC (area under the curve), thus constituting a parameter indicative of the influence that cocrystals have on the API performance. The AUC is directly and inversely proportional to the dissolution and precipitation rates, respectively [49]. Figure 7 shows that unformulated NTZ-SUC cocrystals and NTZ-SUC formulated with 1.0% w/w Methocel ® 60 HG do not lead to improved dissolution profiles when compared to NTZ and the Figure 6a illustrates the dissolution profiles measured over a time interval of 3 h of the unformulated (0.0% w/w of Methocel ® 60 HG) solid phases of pure NTZ, the physical mixture with SUC and the NTZ-SUC cocrystal.…”
Section: Of 18mentioning
confidence: 99%
“…There are, however, several reports where differences between kinetic solubility of cocrystals and free forms of drug were observed when dissolution rates of powders were studied. It was observed that there were initial increases in drug concentrations, which decreased with time as the free base forms precipitated out [ 17 , 22 , 23 ]. This is analogous to the supersaturation of amorphous drugs prior to their conversion to crystalline forms [ 24 ]; when the solubility reaches equilibrium, any difference between solubility of cocrystal and free drug form diminishes or disappears.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above-mentioned experimental findings, several investigators have demonstrated through a combination of experimental studies and theoretical calculations that cocrystals can indeed have major solubility advantages over their respective free forms, sometimes by several orders in magnitude [ 22 , 23 , 25 , 26 ]. The higher solubility of cocrystals as the function of pH in these studies were obtained by applying a new 3-step process: first, drug and coformer concentrations in equilibria with cocrystals were measured at pH values of interest; second, cocrystal solubility and solubility product ( K sp ) were determined from the measured equilibrium concentrations; and, third, the pH dependence of cocrystal solubility is theoretically calculated from K sp of cocrystal, p K a values of drug and coformer, and corresponding solubility equations [ 22 ]. Based on such theoretical calculations, Chen et al [ 22 ] observed much higher solubility for 1:1 cocrystals of ketoconazole, a basic drug (p K a 2.94 and 6.51) [ 27 ], with fumaric acid, succinic acid and adipic acid in the pH range of 4 to 7 as compared to that of the free base in the same pH range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocrystallization of basic drugs, such as INH, with acidic coformers can mitigate these effects. [17] Moreover, the degradation of RIF and INH due to hydrazone formation in FDC may potentially be countered by masking the hydrazide group through cocrystallization, as well as allowing INH to be combined with an antioxidant in a single tablet. In this present study, hydroxyl derivatives of cinnamic acid were employed to synthesize new cocrystal forms of INH (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%